Rosyjska straszna bajka. Potencjał krytyczny estetyki „posthorroru” grupy artystycznej Ic3peak - Jewdokimow, Dorota (Humaniora. Czasopismo Internetowe, 2024)
The content of the article is an application and development of Yuri Lotman’s concepts of cultural emotions, in particular the semiotics of fear. The author assumes that fear as a cultural emotion is encoded, expressed and evoked by art using its own artistic tools. The aim of the article is to indicate how the mechanism of fear can be intercepted by art and incorporated into its subversive potential. The author does this by referring to the work of the Russian artistic group Ic3Peak, which consciously reaches for the aesthetics of “post-horror,” creating a coherent artistic message, as well as their artistic image. The text contains the theses that art mediates fear, depriving it of the real possibility of influence and control. At the same time, by virtue of the ambivalence of horror, which repels and attracts at the same time, mediation can paradoxically lead to the normalization of fear and its romanticization. The work of Ic3peak, apart from its critical function, creates a sense of community of experience, belonging to a larger whole that allows the fans to transcend the fear that paralyzes the individual.